Smart Trip Planner Web Application for Promoting Sustainable Tourism - Sarode, Namith H.; Sameera, K. R.; Tikare, Sanjana K. (International Journal of Research in Interdisciplinary Studies, 2025)
This research paper presents the development of a smart trip planner web application that simplifies travel planning and promotes sustainable tourism. The platform, built using Flask for the backend and standard web technologies (HTML, CSS, JavaScript) for the frontend, integrates AI-powered recommendation systems, real-time data, and user preferences to deliver customized itineraries. In addition to core features like itinerary creation, the system introduces innovations such as hotel booking integration, augmented reality (AR) previews, and a voice-based travel assistant. This paper outlines the motivation, design, methodology, innovations, and expected outcomes of the system while reviewing relevant literature and existing technologies. A development timeline is included to guide implementation.